Development of the Export of Russian Education: Focusing on the Needs of National Labor Markets - A. О. Аver’yanov; V. A. Gurtov; D. N. Semenov; V. I. Kruglov (Высшее образование в России)
Russia ranks fourth in the international education market in terms of the number of foreign students. The export of Russian education contributes to the growth of external financial re[1]ceipts to the economy, facilitates overcoming the personnel shortage in the labor market and forms a positive image of Russia among the countries importing education. The article presents data on the key countries importing Russian education. The authors described the most popular areas of training and specialties among the foreign students, both for enlarged groups of specialties, and for certain areas of training in the context of training levels (bachelor’s / specialty / master’s). The sources of financing the education of foreign citizens in Russian universi[1]ties were considered, as well as foreign student enrollment for each type of financing. In the course of the analysis of the electronic portals of the authorities in the field of labor and employment, as well as statistical agencies, and professional job search websites, the need for certain specialists in the national labor markets of the key countries-importers of Russian education was revealed. Based on these data, the relevance of the education exported by Russia to the needs of the national labor markets of its importers was analyzed. The study revealed an annual growth of foreign student enrollment under the contracts for the pro[1]vision of fee-based education, which increases the volume of external financial receipts into the Russian economy. It is shown that the current level of education exports in Russia corresponds to the strategic state tasks in this direction, and the need for workers in the labor markets of the key importing coun[1]tries coincides with the most demanded areas of training and specialties among foreign students.